Managing Exam Anxiety and Improving Time Management with Digital Platforms - Ekawati, Dessy; Baderi, Baderi (Jurnal Ilmiah Perawat Manado (Juiperdo), 2024)
Introduction: Exam anxiety is a major issue affecting academic performance among students worldwide, primarily due to the pressure to meet high academic expectations and poor time management. Research Objective: This study aims to evaluate the effectiveness of digital platforms (Quizizz, Kahoot!, and Socrative) in reducing exam anxiety and improving time management skills among students at ITSKes ICME Jombang. Method: A quantitative design with a pre-post test approach was used, with a randomly selected sample of 98 students from a population of 130. Data were collected through exam anxiety and time management questionnaires, as well as test results, and analyzed using the Wilcoxon Ranks Test and Kruskal-Wallis Test. Research Results: The findings indicate that digital platform-based interventions significantly improved academic performance, with Quizizz proving to be the most effective platform, as well as reducing anxiety levels and enhancing time management skills. Conclusion: Digital platforms are proven effective in enhancing students' academic performance and time management skills, particularly in helping female students manage exam anxiety through flexible and structured self-study features. Keywords: exam anxiety, time management, digital platform